Impact of Financial Leverage, Growth and Size on the Profitability of Nepalese Commercial Banks - Joshi, Udaya Raj (Nepalese Journal of Economics, 2024)
This study examines the effect of financial leverage, growth, and size on the profitability of Nepalese commercial banks. Return on asset and net interest margin are selected as the dependent variables. Similarly, asset growth, board size, debt to equity ratio, firm size, leverage, and number of branches are selected as the independent variables. This study is based on secondary data of 15 commercial banks with 120 observations for the study period from 2014/15 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, annual reports of the selected commercial banks and reports published by Ministry of Finance. The correlation coefficients and regression models are estimated to test the significance and importance of financial leverage, growth, and size on the profitability of Nepalese commercial banks. The study showed that asset growth has a negative impact on return on assets and net interest margin. It indicates that increase in asset growth leads to decrease in return on assets and net interest margin. In addition, number of branches has a negative impact on net interest margin. It means that increase in number of branches leads to decrease in net interest margin. Likewise, board size has a positive impact on return on assets. It indicates that increase in board size leads to increase in return on assets. Moreover, leverage ratio has a negative impact on return on assets. It indicates that increase in leverage ratio leads to decrease in return in assets of Nepalese commercial banks. Similarly, number of branches have a positive impact on net interest margin. It indicates that increase in number of branches leads to increase in net interest margin. In addition, firm size has a negative relationship with return on assets and return on equity. It means that increase in firm size leads to decrease in return on assets and return on equity.